Sansevieria trifasciata extract effectively inhibit the growth of Escherichia coli bacteria, in vitro - Rachmaniyah, Rachmaniyah; Rusmiati, Rusmiati (Intelektual Pustaka Media Utama, 2023)
Sansevieria trifasciata is a plant that has the potential to kill pathogenic bacteria due to its content. An experimental study with a laboratory experimental design was carried out to test the inhibition of Sansevieria trifasciata extract against Escherichia coli in vitro. Antibacterial testing of Sansevieria trifasciata extract was carried out at concentrations of 5%, 10%, and 40% to explore the growth of Escherichia coli by maceration method and using 96% ethanol. The medium used was Mueller Hinton Agar which had previously been inoculated with the test microbe (Escherichia coli ATCC 25922) and then the results obtained were compared with the control group for comparison. The ethanol extract of Sansevieria trifasciata with concentrations of 5%, 10%, and 40% could inhibit the growth of Escherichia coli bacteria with the average diameter of the inhibition zone respectively 6.63 mm, 5.42 mm, and 6.55 mm compared to the diameter of the Escherichia coli on the control variable + using the previous ciprofloxacin, namely 20.4 mm, 20.8 mm and 20.4 mm. Sansevieria trifasciata has good inhibition against the growth of Escherichia coli bacteria with low or high concentrations.